Drought-induced proline synthesis depends on root-to-shoot communication mediated by light perception - Ferreira Júnior, D. C. [UNESP]; Gaion, L. A. [UNESP]; Sousa Júnior, G. S. [UNESP]; Santos, D. M.M. [UNESP]; Carvalho, R. F. [UNESP] (Springer Nature, 2018)
Proline accumulation in roots and shoots is one of the most evident responses to environmental stresses such as drought, which is currently one of the main threats for agriculture. Based on this response, in this work, we hypothesize that proline accumulation is dependent on root-to-shoot communication through light perception. Thus, we used exaggerated light response (hp1) and phytochrome-deficient (au) mutants of tomato, which were combined through self-grafting and reciprocal grafting and subjected to drought stress, for posterior determination of shoot and root growth and proline content. Light-affected proline metabolism, as hp1, had the highest accumulation, while au presented the lowest proline values. Reciprocal grafting showed that hp1 and MT as scion or rootstock improved MT and au proline content, respectively, indicating shoot-to-root and root-to-shoot communication modulate the metabolism of this compatible osmolyte. Dry weight, leaf area, and root area presented similar patterns to proline content, indicating the importance of this compound for plant growth under stress conditions. These results provide a new perspective on light mediation of long-distance proline translocation in stressed plants.
Keywords: Compatible osmolyte; Drought stress; Light signaling; Phytochromes